2009
DOI: 10.1269/jrr.08132s
|View full text |Cite
|
Sign up to set email alerts
|

Microbeam Irradiation of the C. elegans Nematode

Abstract: The understanding of complex radiation responses in biological systems, such as non-targeted effects as represented by the bystander response, can be enhanced by the use of genetically amenable model organisms. Almost all bystander studies to date have been carried out by using conventional single-cell in vitro systems, which are useful tools to characterize basic cellular and molecular responses. A few studies have been reported in monolayer explants and bystander responses have been also investigated in a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…These results show that similar egg-lethal effects of high energy carbon ions occur before and after hatching, and that high-LET radiation does not additionally induce lethal effects on eggs in the body of C. elegans. This may support the hypothesis that the bystander effect is little if any in the last stage of embryogenesis of germ-line in C. elegans (Sugimoto et al, 2006), although the bystander-induced expression of heat-shock protein HSP-4 was reported (Bertucci et al, 2009). Taken together, we found that eggs of C. elegans were more sensitive to high-LET radiation exposure than to low-LET radiation exposure.…”
Section: Dose Response For Hatchabilitysupporting
confidence: 87%
“…These results show that similar egg-lethal effects of high energy carbon ions occur before and after hatching, and that high-LET radiation does not additionally induce lethal effects on eggs in the body of C. elegans. This may support the hypothesis that the bystander effect is little if any in the last stage of embryogenesis of germ-line in C. elegans (Sugimoto et al, 2006), although the bystander-induced expression of heat-shock protein HSP-4 was reported (Bertucci et al, 2009). Taken together, we found that eggs of C. elegans were more sensitive to high-LET radiation exposure than to low-LET radiation exposure.…”
Section: Dose Response For Hatchabilitysupporting
confidence: 87%
“…[12][13][14][15][16][17][18] However, the underlying mechanisms are far from clear, including the temporal and spatial course of bystander signaling in the context of whole organism.The RIBE in model plant Arabidopsis thaliana has been investigated in our group. After micro-beam irradiation of naked seed embryos and low-energy ion irradiation of intact seeds, some post-embryonic developmental phenotypes were inhibited significantly, which differentiated from bystander shoot apical meristem (SAM) cells or root apical meristem (RAM) cells.…”
mentioning
confidence: 99%
“…Ureter models [55,134], as well as commercially available skin reconstruct models containing both epidermis and dermis or the epidermal layer alone [135][136][137], are classified as tissue models here. Although tissue models can provide some valuable information regarding the non-targeted effects of ionizing radiation in the multicellular tissue environment, it remains necessary to extrapolate such results back to the biology of the whole living organism; thus, there remains a marked advantage to perform the relevant studies in whole organism models [138,139]. As remarked by Bertucci et al [139], studies using whole organisms, which target specific cells, cell groups or organs, would be needed to realistically elucidate the mechanisms underlying the RIBE.…”
Section: In Vivo Studies On Ribe Using Animal Modelsmentioning
confidence: 99%
“…Although tissue models can provide some valuable information regarding the non-targeted effects of ionizing radiation in the multicellular tissue environment, it remains necessary to extrapolate such results back to the biology of the whole living organism; thus, there remains a marked advantage to perform the relevant studies in whole organism models [138,139]. As remarked by Bertucci et al [139], studies using whole organisms, which target specific cells, cell groups or organs, would be needed to realistically elucidate the mechanisms underlying the RIBE. We will hereafter focus on whole organism models when discussing in vivo models.…”
Section: In Vivo Studies On Ribe Using Animal Modelsmentioning
confidence: 99%